Understanding Panic Buying Through an Integrated Psychodynamic Lens - Cooper, Marty A.; Gordon, Jamie L. (Frontiers in Public Health, 2021)
Previous literature has identified panic buying as often being a response to environmental stressors. In early 2020, we saw an increase in panic buying as a response to a real and/or perceived lack of resources due to COVID-19. Although panic buying has a long history, there is a lack of literature to provide a psychological understanding of the phenomenon. During the early days of COVID-19 clients presented with fear and uncertainty. These negative emotions were, in part, a response to a real shortage of basic supplies. However, the panic response led to behaviors that, for some individuals, resulted in atypical buying patterns. From a therapeutic perspective, one can consider behavioral and psychodynamic explanations and interventions, and how this impacts the associated behaviors. This article will focus on psychodynamic understandings of panic buying as a response to events that result in negative emotions. By providing a psychodynamic understanding of panic buying, authors hope to contribute to the therapy of clients presenting with related behaviors and their associated negative affect.